FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU POSTPARTUM PADA MASA PERSALINAN DI RSU VINA ESTETIKA MEDAN TAHUN 2023 - Devi Erlitna; Anna Waris Nainggolan; Imarina Tarigan (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Excessive fear, anxiety, stress or anger can cause slow labor progress. Feelings of tiredness, fear and hopelessness are the result of pre-labor or a prolonged latent phase. Women who are not supported emotionally, or have had difficulties in previous births, can feel anxious and afraid to face labor, resulting in labor without significant progress and labor that is very painful. Age that is too young and too old, too much parity and knowledge is suspected to increase anxiety in mothers. The aim of this research is to determine the factors related to postpartum maternal anxiety during childbirth at RSU Vina Estetica Medan in 2023. This type of research is analytical observational with cross-sectional. The population in this study was all postpartum mothers who gave birth at RSU Vina Estetica Medan for the January-April 2023 period, namely 116 people. The sample taken based on the Slovin formula was 54 people. Data analysis was carried out using statistical tests using chi-square, to see the relationship between the independent variable and the dependent variable. The results of the research show that there is a relationship between age and knowledge of postpartum mothers and anxiety during labor at RSU Vina Estetica Medan in 2023. There is no relationship between parity and anxiety of postpartum mothers during labor. It is recommended that health workers at RSU Vina Estetica Medan provide regular counseling to mothers about childbirth starting at the beginning of the pregnancy check-up, in order to reduce postpartum maternal anxiety..